(untitled) (Research, Society and Development, 2021)
Objective: To investigate the level of knowledge of laypeople about the identification of signs and symptoms and risk factors related to stroke. Materials and methods: Bibliographic research was carried out in international databases, and 9 studies published between the years 2017 and 2021 were selected, comprising the languages English and Portuguese. Results: By analyzing the articles listed, it was noticed that the majority used a questionnaire as an instrument for data collection (88.9%) and face-to-face interviews (66.7%). With regard to signs and symptoms, the main ones addressed by the studies were: weakness or tingling in the face, arm or leg; confusion, speech disorder or language comprehension; change in vision and sudden, severe headache with no apparent cause. As for risk factors, the most addressed were hypertension and smoking. Conclusions: It was observed that the level of knowledge of laypeople about the identification of signs and symptoms and risk factors for stroke is not satisfactory, due to the low educational level of the participants, few educational campaigns and a small link between users and interdisciplinary teams of health.